Nghiên cứu thực nghiệm về cơ chế thúc đẩy hành vi môi trường chủ động của doanh nghiệp tại tỉnh Khánh Hòa, Việt Nam - Phạm Thành, Thái; Trần Thị Thu , Hòa; Lê Văn , Tháp; Hoàng Gia Trí , Hải (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study aims to determine the stakeholder pressures on firms’ proactive environmental behavior. Using a simple random sampling method, the data was collected from a survey of 407 operating businesses in Khanh Hoa province, Vietnam. Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to estimate and test the impact of stakeholder pressures on the firm’s proactive environmental behavior using the SmartPLS 4.0 software package. The main findings indicate that regulatory, social, customer, and internal pressures have positively significant impacts on the company’s proactive environmental behavior. Notably, internal pressure strongly influences the firm’s proactive environmental behavior. The study also proposes several important practical implications to help policymakers and stakeholders in Vietnam promote businesses in adopting environmental responsibility and moving towards sustainability.